2015
DOI: 10.5761/atcs.oa.14-00160
|View full text |Cite
|
Sign up to set email alerts
|

Results of Lung Cancer Surgery for Octogenarians

Abstract: Purpose: Growing number of elderly lung cancer patients reflecting a lengthening life span has become a serious problem. Purpose of this study was to elucidate the short and long-term outcome of the surgery for octogenarians, and to evaluate the role of lung cancer surgery for this high age group. Methods: The patients with lung cancer aged 80 years or more who underwent the surgery at our institute from January 1998 through December 2012 were retrospectively analyzed by chart review, and the operative mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Aelony et al (49) showed that for patients undergoing major lung resections for early stage NSCLC, mortality was 0.45% for those younger than 45 years and 1.2% for patients older than 75 years. Hino (50) showed that octogenarians with postoperative morbidity had significantly poorer prognosis than those without it. A number of risk factors for developing postoperative morbidity have been reported: congestive heart failure, myocardial infarction, male gender, type of operative procedure, extended lymph node dissection, FEV 1 of 40% or less, smoking status, stroke (3,26,27,42) and administration of induction therapy (51).…”
Section: General Considerationsmentioning
confidence: 99%
“…Aelony et al (49) showed that for patients undergoing major lung resections for early stage NSCLC, mortality was 0.45% for those younger than 45 years and 1.2% for patients older than 75 years. Hino (50) showed that octogenarians with postoperative morbidity had significantly poorer prognosis than those without it. A number of risk factors for developing postoperative morbidity have been reported: congestive heart failure, myocardial infarction, male gender, type of operative procedure, extended lymph node dissection, FEV 1 of 40% or less, smoking status, stroke (3,26,27,42) and administration of induction therapy (51).…”
Section: General Considerationsmentioning
confidence: 99%
“…The age of lung cancer patients has been higher on average recently, and in Japan, after consideration of comorbidity, performance status, and mental state, greater numbers of octogenarians have undergone radical surgery, similar to treatment methods applied to younger generations . Surgical morbidity, mortality, and five‐year overall survival rates for octogenarians have been reported as 8.4–38.0%, 1.1–3.6%, and 27.0–65.9%, respectively . In a meta‐analysis of six eligible randomized studies, Berghmans et al .…”
Section: Discussionmentioning
confidence: 99%
“…The patients' characteristics are shown in Tables 1a-c, as previously reported. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] There were no significant differences between the two groups on most variables, except for preoperative diabetes mellitus (DM) (p = 0.0271), tumor size on CT (p = 0.0002), operation time (p <0.0001), length of postoperative hospitalization (p = 0.0003), or pathological tumor size (p <0.0001).…”
Section: Patients' Characteristicsmentioning
confidence: 97%
“…3) In addition, Dominguez-Ventura et al pointed out that congestive heart failure and myocardial infarction both correlated with postoperative mortality and that male gender, operative procedure, a forced expiratory volume for 1 s expressed as a percentage of the forced vital capacity (i.e., FEV 1% ) of 40% or less, smoking status, and stroke increased the risk of postoperative morbidity. 5,6) Hino et al also reported that male gender and non-adenocarcinoma histology were significant risk factors, 14) while Okami et al reported that comorbidity and mediastinal lymph node dissection were associated with poor prognosis and operative risk. 15) Finally, Ogawa et al reported that the age gap, as previously described, was associated with postoperative morbidity.…”
Section: Predictive Factormentioning
confidence: 99%